NILAI BUDAYA DALAM NOVEL RANA RENJANA KARYA PIKO - Nurasfitasari, Ratna; Pratiwi, Wienike Dinar; Suntoko, Suntoko (Universitas Negeri Makassar, 2024)
This research aims to describe the cultural values in the novel Rana Renjana by Piko. This research is qualitative research using the descriptive method of analysis. The research data was taken based on quotations in the novel Rana Renjana by Piko with data analysis techniques in the form of data collection, data reduction, data presentation, and conclusion drawing. The results of the research found in the novel Rana Renjana by Piko six cultural values. The theoretical values include knowledge about meruwat village, studying, animating a dance, and utilizing nature. Economic values relate to occupations such as trading, farmers, bank employees, and dancers. Religious values include belief in God, belief in the supernatural, belief in objects, being polite, never giving up, and respecting parents. Art values include dance, music, and fine arts. Political values relate to the power possessed by the village head, village elders, parents, and dance teachers. Social values include friendship, love, forgiveness, care, responsibility, and mutual cooperation.